Sonic Histories of Occupation Experiencing Sound and Empire in a Global Context - Skelchy, Russell P.; Taylor, Jeremy E. (Bloomsbury Academic, 2021)
This open access book examines how auditory environments in different contexts have contributed to understanding foreign occupation and colonialism, and how they have given rise to historical music cultures. How are sound and music implicated in the control and discipline of people under occupation? Exploring case studies of foreign occupation and colonialism from around the world, Sonic Histories of Occupation seeks to answer these questions and more. Examining how an emphasis on auditory culture adds complexity and nuance to understanding the relationship between occupation and the bodily senses, this book is structured around three conceptual themes: voice and occupation; memory, sound and occupation; and auditory responses to occupation and colonialism. Highlighting case studies in Asia, North Africa, North America and Europe, contributors employ a range of theoretical approaches to examine histories of imperialism and foreign occupation, and the auditory legacies they created, and contribute to a wider dialogue about the relationship between sound and imperial projects across political and temporal boundaries. The open access edition of this book is available under a CC-BY-NC-ND 4.0 license on www.bloomsburycollections.com. Open access was funded by the European Research Council (Horizon 2020, Grant Number 682081).